2018
DOI: 10.1210/en.2018-00379
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Regulation of Cancer Stem Cells in Breast and Gynecologic Cancer

Abstract: It is well established that obesity increases the incidence and worsens the prognosis of women's cancer. For breast cancer, women with obesity exhibit more than a twofold increase in the odds of being diagnosed with cancer, with a greater risk of advanced stage at diagnosis, and ≤40% greater risk of recurrence and death than their normal-weight counterparts. These findings are similar in gynecologic cancers, where women who are obese with a body mass index (BMI) >40 kg/m2 have up to six times greater risk of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 107 publications
1
50
0
1
Order By: Relevance
“…If body fat is extremely low, it affects leptin levels and in turn the menstruation cycle resulting in poor egg quality [98], which underlines the importance of leptin in women's physiology. However, an increasing amount of data suggests a role for leptin in female cancers including breast, cervical, endometrial and ovarian [99]. The effect of leptin expression and its association with BC differs between premenopausal and postmenopausal women.…”
Section: Leptinmentioning
confidence: 99%
“…If body fat is extremely low, it affects leptin levels and in turn the menstruation cycle resulting in poor egg quality [98], which underlines the importance of leptin in women's physiology. However, an increasing amount of data suggests a role for leptin in female cancers including breast, cervical, endometrial and ovarian [99]. The effect of leptin expression and its association with BC differs between premenopausal and postmenopausal women.…”
Section: Leptinmentioning
confidence: 99%
“…In addition, cancer-associated adipocytes secrete chemokines such as Chemokine (C-C motif) ligand 2 (CCL2), which activates NOTCH1 signaling pathway and induces the stemness of the cancer cells [22,33]. Leptin, which is also produced by cancer-associated adipocytes, collaborates with IL-1, and promotes angiogenesis by upregulating expression of VEGF and VEGF receptors [22,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence indicates that the adipokine leptin, a pleiotropic molecule encoded by the obese gene originally known for its role as a regulator of food intake and energy balance in the mammalian central nervous system, plays a crucial role in maintaining cancer in a stem-like state. Indeed, the expression of the leptin receptor (ObR) is a feature of cancer stem cells and its activation is able to regulate several signaling pathways and oncogenes, which are critically implicated in cancer stem cell activity [ 8 , 9 ]. It has been found that human GBM cell lines as well as human primary GBM tissues expressed leptin along with its receptor and their levels correlate with the degree of malignancy [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%